Tools of information and communication technologies in ecological marketing under conditions of sustainable development in industrial regions (through examples of Poland and Ukraine) - Aleksandra Kuzior; Alla Lobanova (Journal of Risk and Financial Management, 2020)
This scientific work analyzes the current state and problems of implementing the concept of sustainable development in industrial regions, in particular, in Poland and Ukraine. Emphasis is placed on slowing down the implementation of the main provisions of this doctrine, in particular, the violation of environmental requirements and non-compliance with ecological standards by industrial enterprises. The aim of the article is to find effective innovative tools for intensifying the process of implementing the strategy of sustainable development in industrial regions. The paper uses theoretical methods-analysis and synthesis, formalization, hypothetical-deductive modeling, mental modeling, systematization and generalization-as well as empirical: observation, description and comparison. The main result of the work is the substantiation of the scientific idea that the implementation of a sustainable development strategy in industrial regions is possible by intensifying the process of ecological marketing through the use of new information and communication technologies (ICT) and their innovative tools-methodologies, digital systems, the Internet, cloud technologies, and systems of product design, manufacture and sale-due to accelerated communication links. The authors' approach to the development of the mechanism of creation and functioning of the single information space (field) of the ecological marketing of the industrial region is offered in this work, and also, the classification of modern ICT and their tools, which it is expedient to use in this mechanism, is carried out. Their purpose and the expected results from the introduction of ecological products for market research, the development of ecological technologies for the life cycles of ecological products and, thus, the impact on the acceleration of sustainable development in industrial regions are determined.
Keywords: 330; digitalization effectiveness; ecological marketing; industrial region; information and communication technology; risks of development; sustainability; technology assessment